Muggletonian–Quaker Debates - Bailey, Richard (Quaker studies, 2011)
The Quaker Christ within necessitated a belief in the immortal soul that was identified with the pre-existent Christ whose body of ‘flesh and bone’ was an immaterial uncreated substance. The Muggletonians stood well within the tradition of orthodoxy by advocating for a Christ whose glorified body of flesh was confined to the bodily form of a man. Fox’s Christ might have been truer to the earliest traditions of Christianity established by St. Paul who was deeply influenced by Greek thought but by the time we reach the seventeenth century Fox was well outside the fold of theological orthodoxy. As long as Fox was alive he and the majority of his followers were considered to hold grossly unorthodox, unbalanced and even blasphemous views about Christ. By focusing on the debates between Quakers and adversaries such as the Muggletonians it becomes apparent that the controversy created by differing ideas of what constituted ‘divine eternal unchangeable substance’ was both fundamental and irreconcilable.